PRE-BUCKLING STRUCTURAL ANALYSIS OF THIN Z-SECTION UNDER UPLIFT LOADING (Journal of Pharmaceutical Negative Results, 2023)
A z-section purlin steel sheet is considered in this paper to understand its structural behavioragainst the wind uplift loading. Generally toUDL is considered for a practical & effectivedesign as main aspect of loading. A verylimited research is done on combined bendingand lateral torsional buckling, so it is importantto investigate the impact of combine loading onthe z-section which is partially restrained andapplied with uplift loading. In this to describelateral torsional behavior and bending, ananalytical model is developed for the z-sectionwhich is partially restrained. Thin walledclassical bending theory is used to derive thebending stress formula for the z-section. Thepresent developed analytical model thencompare with the Eurocode EN1993-1-3 modeland with FEA results.